Applications of computer/telecommunications systems : proceedings of the OECD Seminar, November 13-15, 1972 - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development ; Washington, D.C. : sold by OECD Publications Center, 1975)
a seminar on applications of computer/telecommunications systems held at the organisations for economic cooperation and development in paris
Includes bibliographical references.
eej 15/01/2019
Loans
Keywords: Electronic data processing; Information storage and retrieval systems; Data transmission systems